Transformative Branding: Are Brands Truly Making a Difference? An Exploration Into the Transformative Branding Practices of Real-World Brands. - Mulangath Unnikrishnan, Krishnakala (Auckland University of Technology, 2023)
Transformative branding is a powerful, dynamic, and complex process and a true force for good. Enacting transformative branding can facilitate a more sustainable and equitable market and societal system. But these outcomes are unachievable if the transformative brands are not mobilising the engagement of stakeholders to facilitate the vision built for the transformation. Collaborative coupling is central to enacting transformative branding, thus, is a limiting factor of true transformative branding. Hence, this research aims to explore how brands that claim to be transformative are (mis)using transformative branding as a higher-order dynamic capability to propel market and social changes via leadership and collaborative coupling. This research first differentiates the transformative branding concept from other transformative concepts in the marketing literature through a literature review. The literature review confirms that transformative branding differs significantly from other transformative marketing concepts in terms of its conceptualisation and implementation of the branding process. The theorisation of transformative branding is not based on traditional branding principles (i.e., a firm-centric dyadic perspective); the branding process in transformative branding involves stakeholder collaboration. Therefore, it requires theories that consider the role of various market actors and market and social systems dynamics. Besides, transformative branding integrates prosocial goals into marketing management goals, which is not the case in other transformative marketing concepts. Four real-world brands (Patagonia, TOMS, Tony’s Chocolonely and Whole Foods) that can be prima-facie perceived as transformative were chosen for the case analysis and their publically available data for a period of 2018 to 2022 critically analysed to understand if they are carrying out appropriate market-shaping activities to facilitate the transformations they promised. The case analysis confirmed that these chosen brands enact transformative branding through their unconventional leadership approach and collaborative coupling activities and facilitate positive transformations in the social and market system.
Keywords: Transformative branding; Transformative green marketing; Transformative marketing; Transformative social marketing; hybrid logics; dynamic capabilities; market-shaping; dominant social paradigm; sustainability; system thinking; marketing and society; real-world brands’ transformative capabilities